Curriculum internationalization: focusing on intercultural communication competence in college English courses at local vocational colleges in China - Liang Yinyin; Abdul Said Ambotang (Faculty of Education and Sports Studies Universiti Malaysia Sabah, 2024)
This paper aims to investigate the limitations of college English courses in Guangxi local vocational colleges in developing students' intercultural communication competence. The study selected the Integrated Model of Intercultural Communication Competence (IMICC) from a multicultural perspective as a key indicator to identify gaps in the internationalization of current vocational diploma courses. With the continuous development of globalization and the proposal of China's Belt and Road Initiative (BRI), vocational college graduates need to master intercultural communication skills to adapt to the competence requirements of the global market for the workforce. Using qualitative methods such as interviews, classroom observations, and literature analysis, the study identified gaps in current English curriculum practices and proposed suggestions for improvement. This study proposes some suggestions to improve the internationalization of college English courses and even vocational diploma courses by integrating an international perspective and improving students' intercultural competence, thereby improving competitiveness in the global job market. The results of the study are expected to guide the formulation of policies and programs to better prepare students for the needs of the global work environment.